Gas Hydrate: Environmental and Climate Impacts - Giustiniani, Michela; Vargas Cordero, Ivan de la Cruz; Tinivella, Umberta; Vasilev, Atanas (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue reports research spanning from the analysis of indirect data, modeling, and laboratory and geological data confirming the intrinsic multidisciplinarity of gas hydrate studies. The study areas are (1) Arctic, (2) Brazil, (3) Chile, and (4) the Mediterranean region. The results furnished an important tessera of the knowledge about the relationship of a gas hydrate system with other complex natural phenomena such as climate change, slope stability and earthquakes, and human activities.